(untitled) (Przegląd Religioznawczy – The Religious Studies Review, 2023)
The article is devoted to Washington Gladden, one of the leading figures of liberal Protestantism – a religious movement that developed at the turn of the 19th and 20th centuries in the United States. The times in which Gladden lived were a period of changes taking place in American society, such as capitalist social relations, centralizing banking sector, and developing industry. As a pastor, he also faced these changes as a journalist, leader of the social gospel movement, and creator of liberal Protestantism. Through his sermons, articles, books, and specific charitable and social activities, he aimed to realize the Kingdom of God on earth. The article an-swers questions such as how Gladden understood the church, how he imagined Christianity, and how he created liberal Protestantism. It also explores how the movement functioned and what content it conveyed.